Controls on the formation of microbially induced sedimentary structures and biotic recovery in the Lower Triassic of Arctic Canada - Bond, David P.G.; Wignall, Paul; Grasby, Stephen; Pruss, Sara; Peakall, Jeffrey (GSA Bulletin, 2019)
Microbially-induced sedimentary structures (MISS) are reportedly widespread in the Early Triassic and their occurrence is attributed to either the extinction of marine grazers (allowing mat preservation) during the Permo-Triassic mass extinction or the suppression of grazing due to harsh, oxygen-poor conditions in its aftermath. Here we report on the abundant occurrence of MISS in the Lower Triassic Blind Fiord Formation of the Sverdrup Basin, Arctic Canada. Sedimentological analysis shows that mid-shelf settings were dominated by deposition from cohesive sand-mud flows that produced heterolithic, rippled sandstones facies that pass down dip into laminated siltstones and ultimately basinal mudrocks. The absence of storm beds and any other “event beds” points to an unusual climatic regime of humid, quiet conditions characterized by near continuous run off. Geochemical proxies for oxygenation (Mo/Al, Th/U and pyrite framboid analysis) indicate that lower dysoxic conditions prevailed in the Basin for much of the Early Triassic. The resultant lack of bioturbation allowed the development and preservation of MISS, including wrinkle structures and bubble textures. The microbial mats responsible for these structures are envisaged to have thrived, on sandy substrates, within the photic zone, in oxygen-poor conditions. The dysoxic history was punctuated by better-oxygenated phases, which coincide with the loss of MISS. Thus, Permo-Triassic boundary and Griesbachian mudrocks from the deepest-water settings have common benthos and a well-developed, tiered burrow profile dominated by Phycosiphon. The presence of the intense burrowing in the earliest Triassic contradicts the notion that bioturbation was severely suppressed at this time due to extinction losses at the end of the Permian. The notion that Early Triassic MISS preservation was caused by the extinction of mat grazers is not tenable.